Africa Agriculture Transformation Scorecard: performance and lessons. Zimbabwe - Mupandawana, M.; Greffiths, Jacob Ikhothatseng; Matchaya, Greenwell C.; Fakudze, Bhekiwe; Nicholas, G. N.; Mayoyo, A. (Regional Strategic Analysis and Knowledge Support System for Southern Africa / AKADEMIYA2063, 2023)
This policy brief was developed by the Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa (ReSAKSS-ESA), which is facilitated by AKADEMIYA2063 and the International Water Management Institute (IWMI), and Zimbabwe’s Ministry of Lands, Agriculture, Fisheries, Water, Climate, and Rural Development.